The Construction of Female Identity in Chinese Biographical Film Anita Through the Lens of Male Gaze (Asian Journal of Social Science Studies, 2026)
Anita 《梅艳芳》 is a biopic newly released in 2021, chronicling her journey from a child performer to one ofmost recognized music idols in China and Southeast Asia. Mui began her singing career as a little girl, givingshows at an amusement park. Known as “Asian Madonna”, she kicked off her career by winning a singingcontest in Hong Kong in 1982. Meanwhile, Mui also gained fame as an actress. She starred in more than 40movies over 20 years, winning Taiwan’s Golden Horse award for best actress in 1987 for her role as a tormentedghost in the movie “Rouge.” She was also known for her charity work, setting up the Anita Mui CharityFoundation in 1990s.Biopics generally focus on a non-fictional or historical person, reflecting the characteristics of the social contextby retelling his or her life story in a comprehensive way. Thus, the protagonist Mui and the context she lived inmake Anita a special Chinese biopic. Anita Mui lived in Hong Kong from 1963 to 2003, and she is known as“The Daughter of Hong Kong” for the spirits and culture reflected by her life story. Different from most Chinesebiopics, the protagonist in this film is a female, not a male like Ip Man, Wong Fei Hung or Mei Lang Fang inmost Chinese biopic. Besides, Mui is a modern singer, not a patriotic heroine such as Qiu Jin and Liu Hu Lan, ora feudal empress such as imperial concubine Yang (杨贵妃) and Empress Wu.In a survey of biography up to 1960, George Custen finds that female biopic subjects in the thirties were oftenqueensThe image of Mui as a modern female is complex and multi-dimensional. She is traditional in some way,shouldering heavy family burden, expressing her wish for marriage, while her works broke the commonimpressions toward female at that time. For example, songs like “Bad Girl” caused a ruckus in 1985 with itsbrazen lyrics about female sexual desire. She openly revealed her wish for romantic relationship and marriagelife by saying “My idol is Momie Yamaguchi, who resolutely decide to retire at the height of her career for theone she love”, while at the same time, she presented herself as an independent singer, actress and a philanthropist,revealing her feeling that “I will concentrate on my career development in these years and I don‟t need to settledown yet”. To sum up, Mui‟s life story reflects the muti-dimensional values and dilemmas of Chinese careerwoman, which makes Anita a special biopic in China.